2021
DOI: 10.3233/mnm-200474
|View full text |Cite
|
Sign up to set email alerts
|

Associations between whole and low-fat dairy products consumption, physical performance and mental health

Abstract: BACKGROUND: Military staff are required to be in a proper condition of mental health and weight standards and have a specific level of physical performances (PP). Dairy products are rich sources of essential nutrients. It was demonstrated that Iranians consume much less milk and its products and there is no exception in the military staff. OBJECTIVES: To examine the association between consumption of low or whole-fat dairy and psychological disorders and PP in military personnel. METHODS: This cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Although inconsistencies in measures used to report dairy intake limit comparability between all studies (e.g., grams per day vs times per week), low-fat dairy intake in the present study (mean ± SD intake of 694 ± 188 g/day in the highest tertile) was more than double that of other studies [14]. It is also plausible that these discordant findings could be explained by differences in the categorization of high-and low-fat dairy products, and the proportion of individual dairy products that contribute to overall intake.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Although inconsistencies in measures used to report dairy intake limit comparability between all studies (e.g., grams per day vs times per week), low-fat dairy intake in the present study (mean ± SD intake of 694 ± 188 g/day in the highest tertile) was more than double that of other studies [14]. It is also plausible that these discordant findings could be explained by differences in the categorization of high-and low-fat dairy products, and the proportion of individual dairy products that contribute to overall intake.…”
Section: Discussioncontrasting
confidence: 60%
“…Whereas no significant association was observed between whole-fat dairy intake (≥ 4 times/week) and the prevalence of depressive symptoms [ 13 ]. A further cross-sectional study in Iranian military personnel ( n = 230) similarly reported that higher low-fat dairy intake (mean 338 g/day), but not whole-fat dairy intake, was associated with reduced odds for depressive symptoms [ 14 ]. While it is possible our findings are due to chance, potential explanations for these discrepancies could include our larger sample size, differences in dietary assessment tools, or differences in dairy consumption levels between studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between low-fat dairy products and anxiety was evaluated in 3 Iranian studies with mixed results. One study did not observe any significant associations [ 114 ] and two studies observed significant inverse associations [ 5 , 104 ]. None of these studies specified the precise levels of dairy consumption.…”
Section: Resultsmentioning
confidence: 99%